Seismic structural assessment of a 40 years old melt shop facility - Huaco Cardenas, Guillermo David (2019)
Assessment of old factory infrastructure is required in order to keep them working especially after natural hazard event such as earthquake, tornados, or variation of gravity loads. This type of structure is considered essential since it should be safety for workers during operation time and to avoid possible economical losses if this facility stops its operations after any main seismic event. It is presented the structural assessment of the infrastructure of a melt shop facility, which it used for production of structural steel shapes. This infrastructure was built at the beginning of 80’s and it is located at near Pisco city in Peru. Reinforced concrete C columns and L beams make the frames of the structure and the rood is made by steel trusts. NDT and destructive tests were made for the reinforced concrete members as well of extraction of steel coupons from the roof trusts. Auscultation of foundation, reinforced concrete and steel structures were performed. It was found that several columns present damages such as spalling of cover, impact hits from heavy vehicles, which get in the interior of the facility. The roof presents metallic dust which was accumulated by the smelter operation. Heat of 50 Celsius degrees is the average temperature during the 20hours per day of operation time. Besides, capacity of several reinforced concrete columns and beams, and steel members of the roof is minor that their demands respectively according to Peru and international codes. The performance of the full structure of the melt shop including concrete and steel structures presents allowed drifts according seismic provisions, however this structure behaves on its nonlinear range under demands of Peru seismic code.